Effects of quantitative marinating on meat quality, biogenic amines, and flavor compounds in crayfish meat - Kang, Kelang; Zhang, Fan; Fu, Fuhua; Ouyang, Jie; Wei, Yingjuan; Lin, Shuhua; Jiang, Cheng; Yu, Meijuan; Yang, Hui (Frontiers in Nutrition, 2025)
Stewing is a traditional processing method, commonly used for crayfish meat (Procambarus clarkii). In this study, we used a novel method called quantitative marinating (QM) to reduce industrial waste during crayfish meat processing. The taste, flavor, and aroma of crayfish meat processed by boiling (CON), stewing (SG), and QM were investigated. The results showed that crayfish meat in both SG and QM had higher L* and b* values (P < 0.05). Crayfish meat subjected to QM exhibited significantly greater hardness, gumminess, and chewiness than SG (P < 0.05), which was associated with tightly packed muscle fibers, as observed via scanning electron microscopy. Both QM and SG exhibited lower bitterness and astringency compared with CON, as tested by electronic tongue. A total of 25 types of FAAs content showed significant changes in QM and SG (P < 0.05), with the umami amino acids and total amino acids in QM increased by 19.47 and 52.97%, respectively, compared with SG. The results of flavor 5′-nucleotides showed that GMP, AMP, and IMP in QM increased by 72.87, 48.78 and 51.98% compared with SG, respectively (P < 0.05). Headspace-gas chromatography-ion mobility spectrometry (HS-GC-IMS) identified 31 compounds, with QM having more volatile compounds such as anethole, linalool, and 1-octanol than SG. The levels of biogenic amines of tryptamine, phenethylamine, and histamine in QM decreased significantly compared with SG (P < 0.05). In conclusion, QM significantly improved the meat color, texture profile and taste-related qualities of crayfish meat while reducing the biogenic amines in crayfish meat.